THE EFFECTIVENESS OF PROJECT-BASED LEARNING IN RAISING TERTIARY STUDENTS' PROFICIENCY - KURNIA ULFA (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2024)
English speaking proficiency is a critical skill in both academic and professional contexts, especially for English as a Foreign Language (EFL) learners. Traditional language instruction, which often emphasizes grammar and writing, frequently fails to develop learners’ speaking fluency and confidence. This study investigates the effectiveness of Project-Based Learning (PBL) in enhancing English-speaking skills among first-semester Informatics students at the tertiary level. Grounded in constructivist and communicative language teaching theories, PBL emphasizes real-world communication, collaboration, and learner autonomy. Using a descriptive method, students participated in a one-month instructional project that culminated in video presentations, assessed across five key speaking indicators: comprehension, grammar, vocabulary, pronunciation, and fluency. After a one-month PBL intervention, it was shown that 20% of students reached the highest proficiency level (score 85-90), then 55% performed at an average level (score 75-80), and 25% remained at a lower proficiency level (score 60-70). 100% of students showed improvement: high and average performers improved by 15 points on average, and low performers improved by 10 points. Results showed significant improvement across all proficiency levels, particularly among high- and average-performing students. The findings indicate that PBL effectively improves learners’ speaking abilities by promoting engagement, authentic language use, and confidence. However, lower-performing students may require additional scaffolding and support. This study supports the integration of PBL into EFL curricula to promote more interactive and meaningful language learning experiences.